Identification of interstitial-like defects in a computer model of glassy aluminum. (23rd June 2017) - Goncharova, E V; Konchakov, R A; Makarov, A S; Kobelev, N P; Khonik, V A
Abstract: Computer simulation shows that glassy aluminum produced by rapid melt quenching contains a significant number of 'defects' similar to dumbbell (split) interstitials in the crystalline state. Although these 'defects' do not have any clear topological pattern as opposed to the crystal, they can be uniquely identified with the same properties which are characteristic of these defects in the crystalline structure, i.e. strong sensitivity to applied shear stress, specific local shear strain fields and distinctive low-/high-frequency peculiarities in the vibration spectra of 'defective' atoms. This conclusion provides new support for the interstitialcy theory, which was found to give consistent and verifiable explanations for a number of relaxation phenomena in metallic glasses and their relationship with the maternal crystalline state.